Micro and macropolitical determinants for non-vaccination against COVID-19 in pregnant women in Belo Horizonte - Marina Stuart Marques; Thales Philipe Rodrigues da Silva; Ana Paula Vieira Faria; Nágela Cristine Pinheiro Santos; Janaína Fonseca Almeida Souza; Marla Ariana Silva; Patrícia Feliciano Pereira; Fernanda Penido Matozinhos (Revista Brasileira de Enfermagem)
ABSTRACT Objective: To analyze the determinants for non-vaccination against COVID-19 in pregnant women in Belo Horizonte, Minas Gerais, Brazil. Methods: An epidemiological study with a cross-sectional design was conducted using data from the project titled “Childbirth and Breastfeeding in Children of Mothers Infected by SARS-CoV-2,” developed during the pandemic in the city of Belo Horizonte, Minas Gerais, Brazil. Results: The study sample consisted of 360 pregnant women, of whom 77.89% received the COVID-19 vaccine. External, social, and institutional determinants can influence lower adherence to COVID-19 vaccination, especially the absence of employment during pregnancy, difficult access to prenatal consultations, and a compromised or deficient support network. Conclusions: In light of this scenario, greater encouragement for health education is necessary, especially during prenatal care, resulting in lower rates of morbidity and mortality and favorable perinatal outcomes.